2006
DOI: 10.1097/01.rli.0000197668.44926.f7
|View full text |Cite
|
Sign up to set email alerts
|

Relaxivity of Gadopentetate Dimeglumine (Magnevist), Gadobutrol (Gadovist), and Gadobenate Dimeglumine (MultiHance) in Human Blood Plasma at 0.2, 1.5, and 3 Tesla

Abstract: Gd-BOPTA demonstrates the highest longitudinal r1 at all field strengths, which is ascribable to weak protein interaction. The R2/R1 ratio increases at higher field strength only for Gd-BOPTA, hence very short echo times are required for Gd-BOPTA to benefit from the higher longitudinal relaxivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
330
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(351 citation statements)
references
References 33 publications
15
330
2
4
Order By: Relevance
“…Among the GBCAs currently approved by the FDA, gadobenate dimeglumine (MultiHance; Bracco, Milan, Italy) has proved superior to other GBCAs at equivalent dose for MR imaging of tumors of the CNS. [1][2][3][4][5][6][7][8] The superior diagnostic performance achievable with gadobenate dimeglumine, which is reflected in a recently updated "Summary of Product Characteristics," 9 is due to high in vivo R1 relaxivity (6.3-7.9 L ϫ mmol Ϫ1 ϫ sec Ϫ1 at 1.5T, 10,11 ) which derives from weak and transient interactions of the gadobenate contrast-effective molecule with serum albumin. 12,13 The increased R1 relaxivity leads to increased SI enhancement and thus significantly improved lesion visualization and better depiction of morphologic features relative to those achieved with GBCAs, which do not interact with serum protein, when these agents are administered at an equivalent dose of 0.1 mmol/kg of body weight.…”
mentioning
confidence: 99%
“…Among the GBCAs currently approved by the FDA, gadobenate dimeglumine (MultiHance; Bracco, Milan, Italy) has proved superior to other GBCAs at equivalent dose for MR imaging of tumors of the CNS. [1][2][3][4][5][6][7][8] The superior diagnostic performance achievable with gadobenate dimeglumine, which is reflected in a recently updated "Summary of Product Characteristics," 9 is due to high in vivo R1 relaxivity (6.3-7.9 L ϫ mmol Ϫ1 ϫ sec Ϫ1 at 1.5T, 10,11 ) which derives from weak and transient interactions of the gadobenate contrast-effective molecule with serum albumin. 12,13 The increased R1 relaxivity leads to increased SI enhancement and thus significantly improved lesion visualization and better depiction of morphologic features relative to those achieved with GBCAs, which do not interact with serum protein, when these agents are administered at an equivalent dose of 0.1 mmol/kg of body weight.…”
mentioning
confidence: 99%
“…Whereas both agents have a linear ionic molecular structure and are widely used for CE-MRA, they differ in that gadobenate dimeglumine possesses markedly higher R1 relaxivity in vivo (6.3-7.9 compared with 3.9 -4.1 L ϫ mmol Ϫ1 ϫ second Ϫ1 at 1.5T 9,10 ). Numerous studies across a range of CE-MRA applications have shown that gadobenate dimeglumine is superior to gadopentetate dimeglumine in terms of diagnostic performance and/or contrast enhancement and image quality when these agents are administered at equivalent doses.…”
mentioning
confidence: 99%
“…In this study we compared one of the most widely used gadolinium-containing contrast agents, Gd-DTPA, with the contrast agent Gd-BOPTA. Gd-BOPTA demonstrates a weak and transient binding with serum proteins, thus leading to up to doubled relaxivity under physiological conditions (14). It has proven beneficial for studying liver perfusion and the increased relaxivity improves the image quality of MR angiography, eg, of the renal arteries (16).…”
Section: Discussionmentioning
confidence: 99%
“…One potentially confounding factor is the interaction of the contrast agent and serum proteins. The contrast agent gadobenate-dimeglumine (Gd-BOPTA) demonstrates weak and transient interactions with serum proteins, causing slowing of the molecular tumbling dynamics, resulting in strong increases in the magnetic relaxivity in solutions containing serum proteins, particularly albumin (13,14). Compared to gadopentetate-dimeglumine (Gd-DTPA), in human plasma relaxivity is increased significantly (14,15), which has proven useful for performing, eg, MR angiography of the renal arteries (16).…”
Section: Magneticmentioning
confidence: 99%